IMPLEMENTASI PROSES PEMBELAJARAN BERBASIS KURIKULUM 2013 DI SEKOLAH DASAR NEGERI 014 SUNGAI BARU KECAMATAN GAUNG - Erdawati, Sri; Andryco , Andryco (Alifbata : Jurnal Pendidikan Dasar, 2022)
This study aims to find out how the implementation of the 2013 Curriculum-based learning process in grades IV, V, and VI at 014 Sungai Baru State Elementary School, Gaung District. This type of research is qualitative research. The sample in this study was 3 class teachers at State Elementary School 014 Sungai Baru, Gaung District. The data in this study were collected using observation, interview and documentation techniques. Furthermore, the collected data was analyzed using the percentage formula. The results of data analysis through observation and interviews can be concluded as follows: The implementation of the 2013 Curriculum-based learning process at 014 Sungai Baru State Elementary School, Gaung District, reached the "Good" category. Based on interview data, it is good to implement the 2013 Curriculum-based learning process at 014 Sungai Baru State Elementary School, Gaung District, because: The teacher has carried out the initial activities in learning well. The core activity, learning has been carried out with interesting and varied methods and approaches, so that students' activeness in the learning process is quite developed. In the closing activity, the teacher has also provided relevant evaluations and invited students to draw conclusions.